Effects of Falls Prevention Exercise Program on Gait and Falls Risk in Community-dwelling Older Adults - Puipanichsiri, Paris; Sungkarat, Somporn; Boripuntakul, Sirinun; Jinajin, Sasipa; Nantachai, Gallayaporn; Ruangrukrien, Budnakamol (Journal of The Department of Medical Services, 2022)
Background: Falls are the most frequent and serious problems in community-dwelling older people. Therefore, the effective exercise program to improve balance and prevent falls are necessary.Objective: To examine the effects of falls prevention exercise program on gait and falls risk in community-dwelling older adults.Method: Sixty community-dwelling older adults were allocated into two groups: (1) Participants underwent the falls prevention exercise program for one hour per session, three times per week for three months (experimental group), and (2) Participants received a fall prevention knowledge brochure (control group). Measurements were administered three times: pre-intervention, post-intervention and 1-month follow-up period. 2 x 3 repeated measures ANOVA or Friedman test and Wilcoxon signed-ranks Test were used to analyze data. Significant level was set at p < 0.05.Result: Participants in experimental group performed significantly better in post-intervention and 1-month follow-up period on muscle strength, reaction time, postural sway, PPA score, cadence, gait speed, TUG, anticipatory postural adjustment in first step duration and percent double support time than pre-intervention. Moreover, participants in experimental group performed significantly better on stride length in post-intervention than pre-intervention assessment. Although, this study found better reaction time and PPA score in control group but participants in control group had more fear of falling score in post-intervention than pre-intervention assessment.Conclusion: This falls prevention exercise program can improve gait and muscle strength especially in long term effect which resulted in decrease in falls risk. Therefore, this exercise program is an effective intervention to prevent falls and be able to reduce risk of falls in elderly